Small adipose-derived mesenchymal stromal cells exhibit longer telomeres and enhanced regenerative potential - Berzins, Uldis; Baronins, Janis; Sorokins, Hermanis; Goel, Saurav; Shishkin, Andrei; Zvirgzdina, Rosita; Rautmane, Aija; Minchev, Danail (Frontiers in Bioengineering and Biotechnology, 2026)
Younger, replicative cells with longer telomeres can enhance regenerative therapies, however, there is a lack of a standard method to assess telomere length in live cells. The present study investigated whether the relative size of human adipose tissue-derived mesenchymal stromal cells (AD–MSCs) can influence their telomere length. During early culture, a smaller-sized AD–MSC subpopulation was identified based on characteristic colony emergence. Telomere lengths in total and smaller-sized cell populations were measured. Polymerase chain reaction revealed expression of Nanog and OCT3/4 in small-sized AD–MSCs. Their safety was evaluated in immunodeficient BALB/c nude mice. Smaller AD–MSCs revealed distinct growth properties, with the cell monolayer rolling up into a large aggregate. These cells had longer telomeres (18,121.43 base pairs [bp]) than the total population (15,870.44 bp) and formed teratoma-like structures with skin-like morphology (including hair). In conclusion, AD–MSC size reliably isolates cells with longer telomeres and potential.